Challenges faced by peer support workers during the integration into hospital-based mental health-care teams: Results from a qualitative interview study. (May 2020) - Otte, Ina; Werning, Anna; Nossek, Alexa; Vollmann, Jochen; Juckel, Georg; Gather, Jakov
Background: Being aware of the challenges that may occur during the implementation of peer support work in psychiatry is important to facilitate the integration of peer support workers (PSWs) into multidisciplinary mental health-care teams. Aim: The purpose of this study is to explore the challenges faced by PSWs during their integration into hospital-based mental health-care teams. Methods: Qualitative content analysis of nine open-ended, semi-structured interviews with PSWs is undertaken in five adult psychiatric hospitals in North Rhine-Westphalia, Germany. Results: The analysis of the data revealed three themes: (1) 'Pioneers and the pressure to succeed'; (2) 'a colleague, a rival or yet another patient?' and (3) 'sharing of information, boundaries and professionalism'. All three themes relate to several concrete challenges on different systemic levels and have the potential to impede the PSWs' integration process. Conclusion: Specific implementation strategies which address potential barriers on the different systemic levels should be developed and applied prior to the start of the integration of PSWs into multidisciplinary mental health-care teams.